Strategies for Fermentation Medium Optimization: An In-Depth Review - Singh, Vineeta; Haque, Shafiul; Niwas, Ram; Srivastava, Akansha; Pasupuleti, Mukesh; Tripathi, C. K. M. (Frontiers in Microbiology, 2017)
Optimization of production medium is required to maximize the metabolite yield. This can be achieved by using a wide range of techniques from classical “one factor-at-a-time” to modern statistical and mathematical techniques, viz. artificial neural network, genetic algorithm etc. Each technique has its own advantages and disadvantages, and there are the situations where these techniques are applied for obtaining best results. Use of various optimization techniques in combination also provides the required results. In this article an attempt has been made to review the currently used media optimization techniques applied during fermentation process of metabolite production. Comparative analysis of the merits and the demerits of various conventional as well as modern optimization techniques have been done and logical selection basis has been given in the present review. This review will provide the rationale of selection of suitable technique for the media optimization employed during the fermentation process of metabolite production.